TINJAUAN YURIDIS ANAK KORBAN TINDAK PIDANA DENGAN PELAKU PEDOPHILIA - Aulia Siregar, Yunus; Harahap, Muslim; Ayu Pratitis, Sugih (Jurnal Perspektif Hukum, 2023)
Children are part of the young generation of a nation that has the potential to advance the nation when it grows up. Therefore, children need to be taken seriously. Along with the times, the types of crimes against children are growing. One of them is sexual crimes that are currently rife, which are committed by adults against children or more commonly known as pedophilia. Obscene acts experienced by a child continuously will have a bad impact on the child's physical and psychological development, and it is possible that the child who is a pedophile victim will also become a pedophile in the future. This research is a normative research conducted by collecting primary, secondary and tertiary legal materials through a literature study. The legal materials studied are Law Number 35 of 2014 concerning child protection and the Criminal Code of Law Number 17 of 2016 and legal provisions relating to children. With the existence of legal prosecutors, they can give punishment to perpetrators of sexual crimes against children, considering where the actions of the perpetrators have a bad impact that causes trauma to the victims themselves.